Native ants facilitate the invasion by Delottococcus aberiae in Mediterranean citrus - Plata, Ángel; Gómez-Martínez, María A.; Beitia, Francisco J.; Tena, Alejandro (Springer Nature, 2023)
The invasive mealybug Delottococcus aberiae De Lotto (Hemiptera: Pseudococcidae) has become a key pest in Mediterranean citrus. This mealybug species excretes honeydew that can be consumed by ants, which may give rise to mutualistic relationships and increase the invasibility of this exotic pest. Here, we studied the interaction between D. aberiae and ants in 16 citrus orchards located in the main citrus-growing area of Spain (Valencia) during two consecutive years. Four native ant species were observed feeding on D. aberiae honeydew, and Lasius grandis Forel (Hymenoptera: Formicidae) represented more than 95% of these ants. Lasius grandis was observed attending D. aberiae throughout the year and in all the orchard sites where the mealybug was present. Mealybug colony size had a positive effect on both relative and absolute ant-attendance by L. grandis, but these interactions varied across seasons. Moreover, we found a positive correlation between L. grandis activity and D. aberiae density in all citrus orchards. Our results suggest that the native ant L. grandis and the invasive pest D. aberiae have established a mutualistic association that promotes the establishment and accelerate the invasion of D. aberiae in Spanish citrus orchards. Further research with the aim of evaluating whether the management of this ant species can improve the control of D. aberiae in citrus would be recommended.